An overview of immune checkpoint inhibitors in breast cancer - Federica Miglietta; Maria Silvia Cona; Maria Vittoria Dieci; Valentina Guarneri; Nicla La Verde (Open Exploration Publishing Inc., 2020)
Although breast cancer is not traditionally considered an immunogenic type of tumor, the combination of immunotherapy and chemotherapy has recently emerged as a novel treatment option in triple-negative subtype in the advanced setting and other similar combinations of immune checkpoint inhibitors with chemotherapy are expected to become part of the neoadjuvant management in the near future. In addition, encouraging results have been observed with the combination of immune checkpoint blockade with diverse biological agents, including anti-HER2 agents, CDK 4/6 inhibitors, PARP-inhibitors. The present review summarized the available evidence coming from clinical trials on the role of immune checkpoint inhibitors in the management of breast cancer, both in advanced and early setting.